Arquitectura sensorial como factor de diseño en el espacio público (2020)
Research work on Sensory Architecture as a Design factor in Public Space for people with sensory, cognitive and motor disabilities. With the general objective of designing an accessibility manual for this type of population based on Sensory Architecture to achieve activation of the senses and social inclusion, on the other hand, this project aims to sensitize readers about the proper execution of public space and their inclusion challenges before all kinds of population. In the findings of this research, we managed to understand Sensory Architecture as a design concept that allows us to harmonize materials, colors, textures, objects, lighting, aesthetics, and functionality, allowing us to create spaces with energy and perception and sensation. to the human being. Consequently, the design of the manual can be carried out harmonizing all the components of the public space and that people with disabilities are taken into account in the same intervention. This research contributes to knowledge and allows new fields of exploration in Architecture.